Analysis of Classroom Design with an Energy Efficiency Lighting System - Omar, Nur Izzati; Mohd Jamail, Norakmal; Qamarul Ezani Kamarudin, (Evolution in Electrical and Electronic Engineering, 2024)
Classroom design plays a crucial role in creating optimal learning environments for students. Traditional lighting systems, such as fluorescent lamps, can be less efficient and negatively affect student performance and health. To address this issue, a case study was conducted in a seminar room at University Tun Hussein Onn Malaysia (UTHM). The DIALux Evo software was used to validate outcomes and replicate the illumination setting. The work involves modeling the classroom space selected appropriate lighting fixtures, and configured the lighting system to meet recommended illumination standards while optimizing energy consumption. Clean energy could lower electricity costs, reduce the environmental impact of fluorescent lighting, and promote sustainable growth. This case study's main goal is to figure out the classroom's minimum lamp based on the standard illuminance level and design an energy-efficient lighting system with sustainable practices. Following the implementation of the lighting retrofit, the revised lighting configuration has the potential to conserve up to 305.28 kWh or 72.60% of energy monthly. Future research could use more models of luminaires to facilitate more lucid and precise contrasting elements and to enhance the research, it is recommended to obtain more comprehensive data of energy consumption patterns, architectural lighting design, and electrical load of the classroom. Energy-efficient lighting in classrooms improves student outcomes and reduces energy consumption educational institutions should adopt energy-efficient lighting systems to improve student outcomes, reduce energy consumption, and contribute to a more sustainable future.